Anthocyanin Incorporated Dental Copolymer: Bacterial Growth Inhibition, Mechanical Properties, and Compound Release Rates and Stability by 1H NMR - Halyna Hrynash; Vinay Kumar Pilly; Alexandra Mankovskaia; Yaoyang Xiong; Getulio Nogueira Filho; Eduardo Bresciani; Céline Marie Lévesque; Anuradha Prakki (Hindawi Limited, 2014)
Objective. To evaluate bacterial growth inhibition, mechanical properties, and compound release rate and stability of copolymers incorporated with anthocyanin (ACY; Vaccinium macrocarpon). Methods. Resin samples were prepared (Bis-GMA/TEGDMA at 70/30 mol%) and incorporated with 2 w/w% of either ACY or chlorhexidine (CHX), except for the control group. Samples were individually immersed in a bacterial culture (Streptococcus mutans) for 24 h. Cell viability (n=3) was assessed by counting the number of colony forming units on replica agar plates. Flexural strength (FS) and elastic modulus (E) were tested on a universal testing machine (n=8). Compound release and chemical stability were evaluated by UV spectrophotometry and 1H NMR (n=3). Data were analyzed by one-way ANOVA and Tukey's test (α = 0.05). Results. Both compounds inhibited S. mutans growth, with CHX being most effective (P<0.05). Control resin had the lowest FS and E values, followed by ACY and CHX, with statistical difference between control and CHX groups for both mechanical properties (P<0.05). The 24 h compound release rates were ACY: 1.33 μg/mL and CHX: 1.92 μg/mL. 1H NMR spectra suggests that both compounds remained stable after being released in water. Conclusion. The present findings indicate that anthocyanins might be used as a natural antibacterial agent in resin based materials.